A Lamellar Yolk–Shell Lithium‐Sulfur Battery Cathode Displaying Ultralong Cycling Life, High Rate Performance, and Temperature Tolerance. Issue 3 (29th November 2021) - Liu, Jinyun; Ding, Yingyi; Shen, Zihan; Zhang, Huigang; Han, Tianli; Guan, Yong; Tian, Yangchao; Braun, Paul V.
Abstract: The shuttling behavior and slow conversion kinetics of the intermediate lithium polysulfides are the severe obstacles for the application of lithium‐sulfur (Li‐S) batteries over a wide temperature range. Here, an engineered lamellar yolk–shell structure of In2 O3 @void@carbon for the Li‐S battery cathode is developed for the first time to construct a powerful barrier that effectively inhibits the shuttling of polysulfides. On the basis of the unique nanochannel‐containing morphology, the continuous kinetic transformation of sulfur and polysulfides is confined in a stable framework, which is demonstrated by using X‐ray nanotomography. The constructed Li‐S battery exhibits a high cycling capability over 1000 cycles at 1.0 C with a capacity decay rate as low as 0.038% per cycle, good rate performance, and temperature tolerance at −10, 25, and 50 °C. A nondestructive in situ monitoring method of the interfacial reaction resistance in different cycling stages is proposed, which provides a new analysis perspective for the development of emerging electrochemical energy‐storage systems. Abstract : An engineered lamellar yolk–shell structure of In2 O3 @void@carbon for the Li‐S battery cathode is developed for the first time to construct a powerful barrier that effectively inhibits the shuttling of polysulfides. The continuous kinetic transformation of sulfur and polysulfides is confined in a stable framework, which is demonstrated by using X‐ray nanotomography. The battery exhibits a long cycling life over 1000 cycles with a capacity fade rate as small as 0.038% per cycle, good rate performance, and temperature tolerance.